Trans-splicing in Higher Eukaryotes: Implications for Cancer Development? - Zaphiropoulos, Peter (Frontiers in Genetics, 2011)
Trans-splicing, the possibility of exons from distinct pre-mRNAs to join together, is still a concept in gene expression that is generally regarded of limited significance. However, recent work has provided evidence that in human tumors trans-splicing events may precede chromosomal rearrangements. In fact, it has been suggested that the trans-spliced molecules could act as “guides” that facilitate the genomic translocation. This perspective highlights the development of the ideas of trans-splicing in higher eukaryotes during the last 25 years, from a bizarre phenomenon to a biological event that is attaining stronger recognition.